Investigative skills in the curriculum of teachers in training: A systematic review - Pastenes Ponce, Gloria Rosario (2024)
The general objective of this systematic review is to analyze the state of the art about the scientific literature on investigative skills in the curriculum and in the teaching-learning processes of teachers in training. This article consists of a systematic review published between 2013 and 2023, in the WoS, Scopus and Scielo databases, following the PRISMA method. A sample was established, in which twenty-four articles were identified. First, a bibliometric analysis of the metadata that emerges from the documents is carried out; a second, more in-depth analysis of the content of the research, findings and investigative skills in the teacher training curriculum was carried out. The conclusions reflect on the integration into the curriculum of the investigative skills necessary in teacher training in its earliest stage for the benefit of the role as a research teacher and the educational system in general.